Challenges and Opportunities Experienced among Middle-Aged Badminton Players during the Home Confinement - Asistio, Emma B.; Furog, Aries N.; Longakit, Jet C. (CV. Literasi Indonesia, 2023)
This study explores the challenges and opportunities encountered among middle-aged badminton players during home confinement. The study employed a descriptive-exploratory qualitative approach. The researcher used semi-structured interviews and non-participatory observation to collect data from six middle-aged badminton players who met the researcher's criteria. The study's findings revealed that the participants were challenged during home confinement, influencing their athletic performance and health condition. They pointed out that during home confinement, middle-aged badminton players encountered challenges that included barriers to improving skills, playing the sport, and health risk factors such as poor lifestyle, seclusion, anxiety, and stress. Playing the sport was hindered by limited experience with peers and limited access to facilities and equipment. More time and practice impeded skill improvement. However, the challenges faced during home confinement motivated the players to seek self-improvement opportunities and enhance their physical and social well-being. The study's results emphasize the need to recognize the effects of pandemics on middle-aged badminton players' performance and well-being. This information is crucial for future research to develop appropriate solutions for individuals facing similar challenges during the pandemic or similar events.